Women's employment, children and transition: an empirical analysis on Poland - Elena Bardasi; Chiara Monfardini (Free University Berlin, Jean Monnet Centre of Excellence, 2004)
The effect of transition from centrally planned to market economies on female employment is unclear a-priori. Many studies have pointed out that the emergence of labour markets created obstacles to but also new opportunities for women's employment. A frequently mentioned potential explanation of the lower female participation during the transition period is represented by the reduction of childcare facilities, which created a major constraint on the participation of women with dependent children. However, we must not forget the effect of forces of opposite sign, first of all the household necessity of having two earners during the turbulent transition period. The aim of this paper is to give an empirical assessment on how the transition to a market economy affected the relationship between motherhood and labour force outcomes in Poland. We estimate random effects probit models on two PACO panel datasets covering a four year period before the reform (1987-1990) and a three year period afterwards (1994-1996). Our findings indicate that during transition small children were much less of a deterrent to the employment probability of their mother than it was before transition.
Keywords: J13; J22; P23; C23; 330; female employment; fertility; transitional economies; Poland; panel data; Frauenerwerbstätigkeit; Übergangswirtschaft; Fruchtbarkeit; Kinderbetreuung; Panel; Polen